PENINGKATAN KANDUNGAN P2O5 PADA PUPUK POSPAT ALAM DENGAN AKTIVASI YEAST (SACCAROMYCES CEREVICEAE) - Supriyo, Edy (Vocational School Diponegoro University, 2010)
Edy Supriyo, Mountainous area of Kendeng is known rich with their natural resources, one of which is phosphate. Phosphate element in form of tricalsium phosphate is not dissolved in water therefore it needs to be activated become monocalsium phosphate which is able to be dissolved in the water and can be used for plant to strengthen their root. As activator in hydrolisa reaction is yeast Saccaromyces cereviceae . The result of present work revealed that activation could be done using yeast after being in peak population. Optimum cultivation of yeast using 14o brix molasses give population of 1.8x.107 colonies/cm2. The optimum phosphate (P2O5) concentration increnement happened in subtrate of yeast of 120 grms that is 3,06 %. Key words : Activation, Natural Phosphate Fertilizer